Aplicación del proceso de atención de enfermería en paciente pediátrico con VIH atendido en el Hospital Teófilo Dávila. - Vargas Zaritama, Gina Tatiana (Machala : Universidad Técnica de Machala, 2019)
HIV (human immunodeficiency virus) over time has been one of the most controversial health situations from the point of view of social, political and especially doctor. The state governments and national health systems have invested countless resources to maintain a control in the spread of the virus. HIV is a micro-organism that attacks, affects and destroys CD4 cells, as well as to other elements of defense that has the immune system. The virus adopts a response that allows it to evade or escape the immune action of our body. HIV infection produces a significant deterioration of the function and immune response. Tuberculosis is one of the most at risk diseases because the bacteria is transmitted from one person to another by expectorating the so-called Fluggë Droplets, infecting a healthy person and is caused by the Mycobacterium Tuberculosis bacteria.
El VIH es un microorganismo que ataca, afecta y destruye a los linfocitos CD4, así como también a otros elementos de defensa que tiene el sistema inmunitario. El virus adopta una respuesta que le permite evadir o escapar de la acción inmunológica de nuestro cuerpo. La infección por el VIH produce un deterioro significativo de la función y respuesta inmunológica. La tuberculosis es una de las enfermedades con más riesgo debido a que la bacteria se transmite de una persona a otra por la expectoración de las llamadas Gotitas de Fluggë, infectando a una persona sana y es causada por la bacteria Mycobacterium Tuberculosis.
Keywords: VIRUS DE INMUNODEFICIENCIA HUMANA; TUBERCULOSIS; CITOMEGALOVIRUS; TRANSMISIoN DEL VIH